Longitudinal assessment of high blood pressure in children with nonalcoholic fatty liver disease. - Jeffrey B Schwimmer; Anne Zepeda; Kimberly P Newton; Stavra A Xanthakos; Cynthia Behling; Erin K Hallinan; Michele Donithan; James Tonascia; Nonalcoholic Steatohepatitis Clinical Research Network (PLoS ONE)
Objective Nonalcoholic fatty liver disease (NAFLD) affects 9.6% of children and may put these children at elevated risk of high blood pressure and subsequent cardiovascular morbidity and mortality. Therefore, we sought to determine the prevalence of and risk factors for high blood pressure in children with NAFLD. Methods Cohort study performed by the NIDDK NASH Clinical Research Network. There were 484 children with NAFLD ages 2 to 17 at enrollment; 382 children were assessed both at enrollment and 48 weeks afterwards. The main outcomes were high blood pressure at baseline and persistent high blood pressure at both baseline and 48 weeks. Results Prevalence of high blood pressure at baseline was 35.8% and prevalence of persistent high blood pressure was 21.4%. Children with high blood pressure were significantly more likely to have worse steatosis than children without high blood pressure (mild 19.8% vs. 34.2%, moderate 35.0% vs. 30.7%, severe 45.2% vs. 35.1%; P = 0.003). Higher body mass index, low-density lipoprotein, and uric acid were independent risk factors for high blood pressure (Odds Ratios: 1.10 per kg/m2, 1.09 per 10 mg/dL, 1.25 per mg/dL, respectively). Compared to boys, girls with NAFLD were significantly more likely to have persistent high blood pressure (28.4% vs.18.9%; P = 0.05). Conclusions In conclusion, NAFLD is a common clinical problem that places children at substantial risk for high blood pressure, which may often go undiagnosed. Thus blood pressure evaluation, control, and monitoring should be an integral component of the clinical management of children with NAFLD.